PENANAMAN KEMANDIRIAN SANTRI MELALUI KONSEP AMAL SALEH DI PONDOK PESANTREN DARUL ULUM - Fuji Pratami; Siti Khodijah (Edu Global : Jurnal Pendidikan Islam, 2021)
The purpose of this study is to provide an overview of the inculcation of student independence carried out by the teacher through the habituation of the good deeds of students at the Darul Ulum Islamic Boarding School as well as the supporting and inhibiting factors in its implementation. This research is a qualitative research with a phenomenological approach because it will describe certain facts in detail and depth. Research data were collected by means of observation; interview or conduct direct questions and answers with students and teachers on duty at Darul Ulum Islamic Boarding School; and documentation. Data analysis using descriptive qualitative, namely describing data from interviews from informants as a whole. The main informants were 12 teachers and 83 students of class VI. While the supporting informants are supporting documents related to the independence of students through the concept of good deeds in Islamic boarding schools. The results of this study are. The planting of self-reliance education for students through the concept of good deeds at the Darul Ulum Islamic Boarding School Muara Mais Jambur, namely: (1) making a commitment between teachers and students; (2) students are independent in personal activities; (3) the teacher monitors, provides examples, rewards and punishments to students. The supporting factors for the implementation of the inculcation of santri independence education through the concept of pious charity, namely: maximum teacher performance in monitoring and fostering students, good interaction between fellow stakeholders, facilities and infrastructure that support and support student activities, and support from the surrounding community. The inhibiting factors for the implementation of the inculcation of santri independence education through the concept of pious charity, namely: lack of awareness of students, students who have not been able to manage time as well as possible, the emergence of a sense of laziness in students, and the use of dormitory facilities that are not good.